2002
DOI: 10.4269/ajtmh.2002.66.76
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Rickettsia conorii and Rickettsia typhi infections in the population of northern Greece.

Abstract: Abstract. Seroepidemical surveys concerning the prevalence of Rickettsia conorii and Rickettsia typhi have never been studied in northern Greece. We examined 1,584 sera samples from residents of northern Greece for the detection of antibodies to R. conorii and to R. typhi by means of immunofluorescence assay. In addition, we compared the prevalence of rickettsial infections among the demographic variables of sex, age, occupation, and area of residence. Antibodies to R. conorii and R. typhi were found in 125 (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
8
2
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 14 publications
9
8
2
3
Order By: Relevance
“…However, Brazil is considered as risk area for murine typhus according to a previous report (Parola et al 1998). Murine typhus has been considered a neglected rickettsiosis worldwide (Walker 2004a) and available data from Europe (Daniel et al 2002) and Asia (Tay et al 2003) showed higher rates than in our study. Our results do not support the concept of risk area for R. typhi infection in this Brazilian region.…”
Section: Discussioncontrasting
confidence: 53%
“…However, Brazil is considered as risk area for murine typhus according to a previous report (Parola et al 1998). Murine typhus has been considered a neglected rickettsiosis worldwide (Walker 2004a) and available data from Europe (Daniel et al 2002) and Asia (Tay et al 2003) showed higher rates than in our study. Our results do not support the concept of risk area for R. typhi infection in this Brazilian region.…”
Section: Discussioncontrasting
confidence: 53%
“…This is also reflected in the significant and progressive higher prevalence of past infections in older subjects, which constituted an independent risk factor, and which is probably explained by the longer exposure time experienced by older people. 6 According to living areas, the significantly higher prevalence in rural areas (10.8%) is concordant with the classical distribution of the reservoirs and vector of R. conorii in our environment, and with the epidemiology of cases of Mediterranean spotted fever, which predominate in these areas. 5 In the city, past infections were distributed mainly in the peripheral suburbs of the city, probably due to the presence of open spaces and green zones in which the peridomestic life-cycle of Bar29 strain is more likely to be efficient.…”
Section: Discussionsupporting
confidence: 74%
“…Türkiye'nin Trakya yöresini de kapsayan kuzey Yunanistan'da R. conorii ve R. typhi antikor prevelansı genel populasyonda IFA ile tanımlanmaktadır. R. conorii ve R. typhi antikorları sırasıyla %7,9 ve %2 olarak bulunmuştur (9) . R. conorii antikor prevelansı artan yaşla birlikte, korele olarak artmakta ve erkeklerde istatistiksel olarak yüksektir (9) .…”
Section: Discussionunclassified
“…R. conorii ve R. typhi antikorları sırasıyla %7,9 ve %2 olarak bulunmuştur (9) . R. conorii antikor prevelansı artan yaşla birlikte, korele olarak artmakta ve erkeklerde istatistiksel olarak yüksektir (9) . Kentsel alanlarla kıyaslandığında kırsal alanlarda ve çiftçiler-de R. conorii antikor prevelansı belirgin olarak daha yüksektir (8) .…”
Section: Discussionunclassified